2017
DOI: 10.1186/s13014-017-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

RapidPlan head and neck model: the objectives and possible clinical benefit

Abstract: BackgroundTo evaluate a knowledge based planning model for RapidPlan (RP) generated for advanced head and neck cancer (HNC) patient treatments, as well its ability to possibly improve the clinical plan quality. The stability of the model was assessed also for a different beam geometry, different dose fractionation and different management of bilateral structures (parotids).MethodsDosimetric and geometric data from plans of 83 patients presenting HNC were selected for the model training. All the plans used volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 24 publications
(28 reference statements)
5
79
0
Order By: Relevance
“…Results from our study indicate no benefit for the contralateral parotid in separating parotid data into ipsilateral and contralateral when constructing models, with a potential improvement in ipsilateral doses. This is similar to results from Fogliata et al who also found little difference in the parotid doses between models. There were also no significant trade‐offs between the results of the OAR's produced by both models which can be seen in Table .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results from our study indicate no benefit for the contralateral parotid in separating parotid data into ipsilateral and contralateral when constructing models, with a potential improvement in ipsilateral doses. This is similar to results from Fogliata et al who also found little difference in the parotid doses between models. There were also no significant trade‐offs between the results of the OAR's produced by both models which can be seen in Table .…”
Section: Discussionsupporting
confidence: 91%
“…The first model, known as the ‘separated model’, contains parotid dose data from previously treated patients separated into contralateral and ipsilateral, while the second model, known as the ‘combined model’, combines the parotid data as one structure called ‘parotids’. Fogliata et al also investigated this comparison in a recent study and found that there was little difference between the two models for the resultant parotid dose. This current study sought to further validate this technique.…”
Section: Introductionmentioning
confidence: 99%
“… 9 An isotropic 5 mm margin was then added to CTVs to obtain the PTVs which were cropped 4 mm inside the body contour to avoid the derma. These cases were planned as described in the study by Gregoire et al 11 , Franzese et al 12 , and Fogliata et al 13 with a SIB fractionation scheme to deliver 2 dose levels of 69.96 Gy to the primary target volume and 54.45 Gy to the elective volume in 33 fractions. The OARs of first priority considered were the parotids, the spinal cord, the oral cavity, and the larynx.…”
Section: Methodsmentioning
confidence: 99%
“…Well‐trained RapidPlan models have outperformed conventional trial and error‐based manual planning by reducing excess organs‐at‐risk (OAR) dose with greater consistency 17, 20, 22, 23, 24, 25, 26, 27, 28, 29, 30. Should the model performance be highly dependent on the library volume31 and average quality of the training plans,17, 32 incorporating the model‐improved constituent training plans into the model (closed‐loop)25 may potentially evolve the model as a cycle of interactive improvement.…”
Section: Introductionmentioning
confidence: 99%